Evaluasi Kualitas Laporan Keuangan dan Praktik Good Corporate Governance Pada Perusahaan Teknologi yang Melayani Publik Secara Massal - Fajar Hafidh Arasy; Ignatius Roni Setyawan (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2026)
The digital economy is driving the growth of PT GoTo Gojek Tokopedia Tbk., but the company recorded significant losses post-IPO (2021-2022) due to its "cash burn" strategy and stock-based compensation (SBC) expenses. This condition raises issues of financial reporting transparency and the effectiveness of Good Corporate Governance (GCG) in mitigating agency conflicts. This study aims to evaluate the quality of SBC and marketing expense reporting, and analyze the effectiveness of GCG in protecting public shareholders. The research approach is qualitative with a case study method on secondary data (financial and annual reports post-IPO). Data analysis uses a descriptive-qualitative approach based on PSAK standards (102, 107, 109, 113, 201) and GCG principles. The results show that GoTo has implemented transparency and good reporting quality in accordance with PSAK standards. SBC and marketing expenses are disclosed in detail, reflecting an accurate economic representation. Although still experiencing a net loss, there is a trend of improving performance in the form of a significant reduction in operating losses in 2025 through operational efficiency.